Combined use of biochemical and volumetric biomarkers to assess the risk of conversion of mild cognitive impairment to Alzheimer’s disease - Nesteruk, Marta; Nesteruk, Tomasz; Styczyńska, Maria; Mandecka, Monika; Barczak, Anna; Barcikowska, Maria (Folia Neuropathologica, 2016)
Introduction : The aim of our study was to evaluate the usefulness of several biomarkers in predicting the conversion of mild cognitive impairment (MCI) to Alzheimer’s disease (AD): β-amyloid and tau proteins in cerebrospinal fluid and the volumetric evaluation of brain structures including the hippocampus in magnetic resonance imaging (MRI). Material and methods : MRI of the brain with the volumetric assessment of hippocampus, entorhinal cortex, posterior cingulate gyrus, parahippocampal gyrus, superior, medial and inferior temporal gyri was performed in 40 patients diagnosed with mild cognitive impairment. Each patient had a lumbar puncture to evaluate β-amyloid and tau protein (total and phosphorylated) levels in the cerebrospinal fluid. The observation period was 2 years. Results : Amongst 40 patients with MCI, 9 (22.5%) converted to AD within 2 years of observation. Discriminant analysis was conducted and sensitivity for MCI conversion to AD on the basis of volumetric measurements was 88.9% and specificity 90.3%; on the basis of β-amyloid and total tau, sensitivity was 77.8% and specificity 83.9%. The combined use of the results of volumetric measurements with the results of proteins in the cerebrospinal fluid did not increase the sensitivity (88.9%) but increased specificity to 96.8% and the percentage of correct classification to 95%.